Monitoring the Quality of Life in Dyspeptic Children with KINDL Scale - Ezgi Kıran Taşcı; Özlem Bekem Soylu; Onur Taşcı; İlker Günay; Erhan Eser (Galenos Yayinevi, 2022)
Aim:We aimed to evaluate quality of life in functional and organic dyspepsia and its change during follow-up.Materials and Methods:Children between 4-17 years of age with dyspeptic complaints were enrolled into this study. Organic and functional dyspepsia were differentiated based on clinical findings and the findings of upper gastrointestinal endoscopy, if performed. The Kinder Lebensqualität Fragebogen (KINDL) questionnaire was conducted when the patients were referred to hospital and at their 1st and 3rd month visits, prospectively. Both groups were compared with regard to their demographic data, symptoms and quality of life scores. Factors which affected the KINDL results and any changes in the KINDL scores during follow-up were evaluated.Results:The study group consisted of 71 functional dyspepsia and 65 organic dyspepsia patients. The mean quality of life scores in the physical wellness and school subscales were higher among the functional dyspepsia patients. The total score of the functional dyspepsia group was higher. There was no relation between the individual's gender, their number of symptoms and their KINDL scores. At the first month visit, the total scores and mean scores of the self-esteem, family, school and friends subscales were higher in the functional dyspepsia group. At the third month visit, the mean self-esteem score was higher in the functional dyspepsia group. Total scores increased significantly during follow-up in both the organic dyspepsia and functional dyspepsia groups. This increase was higher in the organic dyspepsia group.Conclusion:Quality of life in both functional dyspepsia and organic dyspepsia patients is affected; applying recommendations and treatment increased the quality of life of both groups. A quality of life scale can be used to monitor response to treatment.